(untitled) (Annals of Medical Research, 2024)
Chronic atrial and intestinal dysrhythmia (CAID) syndrome is a rare disorder affecting the heart and digestive systems. It results in bradycardia and arrhythmia due to sinoatrial node involvement. Concurrently, intestinal pseudo-obstruction arises from anomalies in the Cajal cells, recognized as the pacemakers of the intestine. Patients may experience dizziness, drowsiness, syncope, and palpitations attributed to the arrhythmia, while abdominal pain, distension, vomiting, and constipation can occur due to intestinal pseudo-obstruction. This report discusses the treatment management for two patients diagnosed with CAID syndrome.